Garden—non-garden. Contemporary trends in transformation of greenery as an instrument in the contest for the city - Gawryszewska, Beata J. (Polskie Studia Krajobrazowe, 2019)
The aim of the paper is to characterize contemporary transformation of urban greenery, which rely on the image of garden in order to arrive at a “garden-like” character of the cityscape. It also demonstrates how the image of garden is applied in the city as a new tool of social communication in the course of democratic transformation of the urban space. The author discusses the origins of the garden-image and the “garden-like” character of space, providing examples of how it is used today in the cityscape by the inhabitants, activists, designers and artists. The text introduces a range of informal, Polish projects of urban gardens and spaces drawing on its image, describing their novel role in building the vernacular landscape of a city.